Pengembangan Media Ular Tangga Berbasis QR Code Materi Sumber Daya Alam - Estiana, Illa; Nugraha, Aldila Wanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The research was based on the use of textbook materials and assigning tasks in accordance with the textbook, which made the class less active and boring. This QR Code Snake and Ladder-based learning media aims to teach activities and the use of media while playing in IPAS lessons about natural resources. This research used the ADDIE research model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The research results show that the media validation is 95.45% and the material validation is 96.25%, which is categorized as highly valid. The practicality of the media, based on teacher questionnaires, is 97.05% and student responses are 97.07%, which is categorized as highly practical. The research results indicate that the QR code-based snake and ladder media is highly valid and practical for use in natural resource learning in fifth grade.